2011
DOI: 10.1186/1756-0500-4-372
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and socio-demographic correlates for serious injury among adolescents participating in the Djibouti 2007 Global School-based Health Survey

Abstract: BackgroundMental health and injury are neglected public health issues especially in low-income nations. The objective of the study was to determine the prevalence and socio-demographic correlates for serious injury in the last 12 months.FindingsThe study used data of the 2007 Djibouti Global School-based Health Survey. Logistic regression analysis was used to establish associations. Of the 1, 777 respondents, 61.1% (63.2% males and 57.8% females) reported having sustained serious injury (SSI). Compared to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 15 publications
12
27
0
Order By: Relevance
“…We have observed that boys had significantly higher injury proportion than girls and that the injury rate decreased when age increased. These observations were a constant in all studies regardless the localizations of these studies [7] [34]. These results may reflect, according to Wilson [35] and colleagues, societal norms where boys are allowed more freedom than girls to explore their environments.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…We have observed that boys had significantly higher injury proportion than girls and that the injury rate decreased when age increased. These observations were a constant in all studies regardless the localizations of these studies [7] [34]. These results may reflect, according to Wilson [35] and colleagues, societal norms where boys are allowed more freedom than girls to explore their environments.…”
Section: Discussionsupporting
confidence: 49%
“…Finally, these data can help to identify the injuries that were not medically treated because it is known that even "small accidents" carry information towards a better prevention [15]- [17]. Based on the fact that Peltzer [13] and colleagues have found a large range in terms of variations of the injury's prevalence (from 38.6% in Swaziland to 71.5% in Zambia), we are in accordance with Muula [7] and colleagues which reported that each country needs to document the epidemiology of its injuries. Next to this, Pickett [18] and colleagues have shown, based on the analyses of the data from some countries participating to the Health Behavior in School-aged Children Study, that there was a link between injuries and (multiple) risk behavior.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations